Acoustic Waves Coupling with Polydimethylsiloxane in Reconfigurable Acoustofluidic Platform - Jeongeun Park (Advanced Science, 2024)
Abstract Acoustofluidics is a promising technology that leverages acoustic waves for precise manipulation of micro/nano‐scale flows and suspended objects within microchannels. Despite many advantages, the practical applicability of conventional acoustofluidic platforms is limited by irreversible bonding between the piezoelectric actuator and the microfluidic chip. Recently, reconfigurable acoustofluidic platforms are enabled by reversible bonding between the reusable actuator and the replaceable polydimethylsiloxane (PDMS) microfluidic chip by incorporating a PDMS membrane for sealing the microchannel and coupling the acoustic waves with the fluid inside. However, a quantitative guideline for selecting a suitable PDMS membrane for various acoustofluidic applications is still missing. Here, a design rule for reconfigurable acoustofluidic platforms is explored based on a thorough investigation of the PDMS thickness effect on acoustofluidic phenomena: acousto–thermal heating (ATH), acoustic radiation force (ARF), and acoustic streaming flow (ASF). These findings suggest that the relative thickness of the PDMS membrane (t) for acoustic wavelength (λPDMS) determines the wave attenuation in the PDMS and the acoustofluidic phenomena. For t/λPDMS ≈ O(1), the transmission of acoustic waves through the membrane leads to the ARF and ASF phenomena, whereas, for t/λPDMS ≈ O(10), the acoustic waves are entirely absorbed within the membrane, resulting in the ATH phenomenon.